Desenvolvimento de uma escala para medição de práticas da Produção mais Limpa (P+L) - Borges, Thyago de Melo Duarte (Universidade Federal de São Carlos, 2020)
The increase in materials production and consumption is one of the characteristics of the modern society. This increase, when performed inefficiently, results in the negative environmental impacts on the planet. In this context, it is important to highlight the activities from the industries. Since they are considered as one of the main agents responsible for the increase of such impacts. An alternative to solve this problem is the adoption of the Cleaner Production (CP), a strategy that aims to reduce the environmental impacts by investigating the origin of its causes and proposing practices that eliminate or reduce the generation of these impacts. In order for these companies properly manage these practices, it is necessary that they check and measure the level of implementation of such practices, using for that purpose an instrument (scale) which allows this measurement. In this context, the objective of this thesis is the development of a scale which measure the level of CP practices implementation. The methodological approach used for this objective was mixed, which included the steps necessary to develop a scale : specification of theoretical domains and operational definition of constructs, generation of items, face validation, pre-test and scale purification, reliability and validity analysis of the scale. With this methodological approach, it was possible to create a scale with 08 constructs and 25 practices. This model was validated in terms of construct reliability, convergent validity and discriminant validity. In theoretical terms, this research is relevant because it fills a gap in the literature by developing a scale that measures CP practices in the companies. In practical terms, this research is also relevant because each company can analyse its own performance and extract informations to guide the company´s environmental management. It also possible the utilization of this scale as a bechmarking tool between companies from the same sector or from differents ones.
Development of a scale for measuring cleaner production practices
Keywords: Produção mais Limpa; Práticas; Medição; Medidas; Desenvolvimento de escala; Cleaner production; Practices; Measures; Measurement; Scale development; ENGENHARIAS::ENGENHARIA DE PRODUCAO